Prostate-Specific Membrane Antigen-Targeted Antibody–Drug Conjugates: A Promising Approach for Metastatic Castration-Resistant Prostate Cancer - Chia-Hsien Shih; Tzuo-Yi Hsieh; Wen-Wei Sung (Cells)
Prostate cancer (PCa), especially metastatic castration-resistant prostate cancer (mCRPC), is a significant cancer characterized by its poor prognosis and limited treatment options. Prostate-specific membrane antigen (PSMA) has emerged as a diagnostic and therapeutic target for PCa due to its restricted expression in malignant prostate tissues. In this case, several PSMA-targeting molecules were developed for radiotherapy and immunotherapy. Antibody–drug conjugates (ADCs) are a novel therapeutic approach for various carcinomas that can selectively target PSMA-positive tumor cells and minimize off-target toxicity. ADCs have made great progress in the treatment of breast and bladder cancers, and some have received FDA approval for target therapy. However, studies on PSMA ADCs are limited, and most clinical trials are at stage I or II. Therefore, this study reviewed trials about PSMA-targeting ADCs for the treatment of PCa. Clinical trials have reported a favorable pharmacokinetic profile and antitumor activity. Toxicity studies have revealed manageable adverse effects, with no significant off-target toxicity in PSMA-negative tissues. This study highlights the therapeutic potential of PSMA ADCs for the treatment of mCRPC. However, it also emphasizes the necessity of further clinical investigation to optimize efficacy, safety, and patient outcomes.